THE SITUATION OF URINARY IODINE CONCENTRATION (UIC) AMONG SCHOOL AGE CHILDREN, WOMEN AT REPRODUCTIVE AGE AND PREGNANT WOMEN IN INDONESIA: THE ANALYSIS OF RISKESDAS 2013 - Kartono, Djoko; Atmarita, Atmarita; Jahari, Abas B; Soekirman, Soekirman; Izwardy, Doddy (PERSATUAN AHLI GIZI INDONESIA, 2016)
Iodine Deficiency Disorders (IDD) are the leading cause of goiter, cretinism, developmental delays and other health problems. Iodine deficiency is an important public health issue as it is a preventable cause of intellectual disability. While elimination of iodine deficiency is imperative, it should be noted that excessive intake of iodine can also lead to adverse health effects. This paper analyzed the iodine status using median urinary iodine concentration (MUIC) of school age children (SAC), women of reproductive age (WRA), and pregnant women (PW) who live in the same household from Riskesdas 2013. The total number of households included in the analysis was 13,811 households, from which 6,149 SAC (aged 6 – 12 years), 13,218 WRA (aged 15-49 years), and 578 PW (aged 15-49 years) were enumerated. The national MUIC of SAC, WRA and PWwas in the normal range indicated that the iodine status was adequate using WHO epidemiological criteria. Iodine status in some sub-populations indicated deficiency, however, in terms of geographic characteristics people who live in the urban has better iodine status compared to rural areas. Similarly, populations in richer economic quintiles had better iodine status. Only pregnant women in the 1st and 2nd quintile were deficient. Almost all regions in Indonesia showed the MUIC was in the normal adequate range, except NTT-NTB, Maluku-Papua, and East Java for pregnant women who tend to have lower MUIC (150 µg/L). The status of iodized salt at the household was detected using both Rapid Test Kit/RTK as well as Titration. The result demonstrated a strong association between salt iodine level and iodine status. The MUIC for all three groups were lower when the iodine level in salt was lower, then increased when the levels of iodine content in salt increased. The iodine status of pregnant women consuming non-iodized salt was inadequate. The detrimental effect of iodine deficiency on the mental and physical development of children as well as on the women of reproductive age has been recognized. Indonesia still needs the salt iodization program to keep the iodine status in the normal range. In particular coverage with adequately iodized salt needs to be improved in order to improve the iodine status of pregnant women. For the prevention of Iodine disorders (insufficient), monitoring should be undertaken in regular basis to assess the MUIC, especially for pregnant women.